Sustainability Status of Gillnet Capture Fisheries Based on Economic, Ecological, Technological, Institutional, and Social Aspects in Panipahan Pasir Limau Kapas Sub-District Rokan Hilir District - Simanjuntak, Jeremi Nichola; Brown, Arthur; Zain, Jonny (South East Asian Marine Sciences Journal, 2025)
Rokan Hilir Regency, particularly Pasir Limau Kapas District, has significant potential for capture fisheries. However, ecosystem sustainability depends on high-value fish resources such as senangin and mackerel. Therefore, a sustainable study of fisheries management is needed based on ecological, socioeconomic, community, and institutional dimensions to ensure the sustainable use of fish resources. This research evaluates the sustainability status of gill net capture fisheries in Panipahan, Pasir Limau Kapas District, Rokan Hilir Regency, based on five dimensions: economic, ecological, technological, institutional, and social. The analysis method used is Rapid Appraisal for Fisheries (RAPFISH) with a Multidimensional Scaling (MDS) approach. The results show that the institutional dimension had the highest sustainability index at 92.08%, classified as "sustainable", while the technological dimension had the lowest index at 39.87%, indicating a "less sustainable" status. The economic and social dimensions scored 53.11% and 57.75% respectively, categorised as "moderately sustainable", whereas the ecological dimension scored 43.96%, also "less sustainable". These findings indicate that gill net capture fisheries in Panipahan are not yet fully sustainable, particularly regarding technology and ecology. Therefore, there is a need to enhance environmentally friendly fishing gear use, strengthen local institutional regulations, and increase public education and community involvement to support sustainable fisheries resource management